Introduction to the Special Edition on Administration and Administrators in Canadian Colleges and Universities: The Specificity of Higher Education Administration and Future Directions for Research - Lavigne, Eric; Cowley, Summer (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
This article introduces the Special Edition devoted to Canadian higher education administration and administrators. It situates its contributing articles within the context of the dominant themes noticed in the extant research literature: neo-liberal and managerial shifts, gender and race career asymmetries, macro- and micro-politics, and professional identities; and highlights their salient contributions. It identifies some of the confusion around the specificity of higher education administration and presents a definition that clarifies how administration differs from management, leadership, and governance, as well as circumscribes the role of academic and career administrators in relation to those of administrative staff members. The article closes with recommendations for future research.